The publicity index is a tool for assessing the quality of activities of representative authorities at the regional level - Paladiіhuk, Serhii (Public Administration and Regional Development, 2023)
The article examines approaches to assessing the quality of regional representative authorities (RRAs) at the regional level. It is established that the assessment of the quality of administrative services can be based on the assessment by service consumers (external assessment), assessment by service providers (internal assessment) or mixed assessment (carried out by external entities on the basis of a combination of consumer and provider assessments). It is determined that the quality indicators of the performance of RRAs include indicators of the efficiency of their use of all the resources involved, and are usually quantitative, unlike quality indicators, which are more complex and are quantitative and qualitative, i.e., those that meet the quality standards established in a particular territory. The author proposes to use the publicity index as a tool for assessing the effectiveness of the activities of local self-government at the regional level, which allows monitoring the transparency, openness and accountability of local self-government bodies and officials. It is proved that the uniqueness of the publicity index lies in the fact that, on the one hand, the measurement is comprehensive and a wide range of functions and activities of a municipality is subject to assessment. It is stated that the publicity of local self-government should be understood as a set of managerial and political measures taken by local self-government bodies and officials with a view to ensuring the most open and friendly relations with citizens and increasing the level of general trust in municipal institutions. The main entities to be assessed within the framework of the publicity index are the city mayor (as the chief executive officer), executive bodies of the council (bodies authorized to perform executive and administrative functions) and city council deputies (as the representative body of local self-government). In order to assess the publicity of the RRAs, all indicators were combined into three aggregate component indicators – transparency, openness, and accountability – for each of the monitored objects (city mayor, executive bodies, and deputies). It has been established that to increase the transparency of the RRAs at the regional level, it is necessary to display all public information on the website as much as possible, as well as to report regularly to the community members.